Multi-Ethnic Analysis of Cardiac Pharmacogenetic Markers of Cytochrome P450 and Membrane Transporters Genes in the Russian Population - K. B. Mirzaev; D. S. Fedorinov; D. V. Ivashchenko; D. A. Sychev (Рациональная фармакотерапия в кардиологии)
Aim. To summarize Russian studies using pharmacogenetic testing as applied to cardiology.Material and methods. The authors conducted an online search for articles in December 2018 using the following databases: PubMed, Google Scholar, eLIBRARY. The search was carried out by keywords: "Russia", "Russian", "cardiology" together with the terms associated with the polymorphic marker, including: «P450», «CYP2C19», «CYP2D6», «CYP2B1», «CYP2B6», «CYP2Е1», «CYP2C8», «CYP2C9», «CYP3A4», «CYP3A5», «CYP1A1», «CYP1A2», «CYP4F2», «CYP4F1», «ABCB1», «SLCO1B1», «VKORC1», «GGCX», «SULT1A1», «CULT1», «CES1», «gene», «genes», «pharmacogenetics», «pharmacogenomics», «ethnic group».Results. Generalization of information allowed to identify obscure genes that need to be investigated in pharmacogenetic studies. This information can be used for the development of dosing algorithms and the priority choice of drugs, considering the results of pharmacogenetic testing and planning future research.Conclusion. The results of the literature review indicate the importance of studying the most clinically valid and clinically useful pharmacogenetic markers (CYP2C19, CYP2C9, VKORC1, SLCO1B1) among various ethnic groups in the Russian Federation. With the accumulation of evidence of clinical validity and clinical utility of other pharmacogenetic markers (CES1, CYP2D6*4, etc.), the problem of interethnic differences in the carriage of clinically significant polymorphisms of these genes identified in previous studies in the Russian Federation increasingly requires attention. The most promising for the introduction into the clinical practice in the Russian Federation in the near future are polymorphic markers of the CYP2C19, CYP2C9, VKORC1 and SLCO1B1 genes.